Vigilant-E: empowering online communities against fraudulent activities - Andrew, Leviana; Mathew, Darrold Hansen; Mohd. Zamri, Norfarahzila; Abdul Latiff, Siti Fatimah; Razal, Izzat Al-Hadi; Borhani, Norshohanimira (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2023)
Introducing Vigilant-E, a groundbreaking shared database combatting online scams through the collaborative efforts of social media users. With the surge in online fraud, this platform stands as a safeguard against scams, fostering a vigilant online community. Vigilant-E empowers users to report and access scammer information, displaying bank and mobile numbers with evidence, curbing future fraud and raising awareness for secure online transactions. Its key features include user reporting, efficient search and verification, and community engagement. Social media users contribute scam details and evidence such as screenshots, conversations from the social media platforms or instant messaging apps, or transaction records, while the platform facilitates swift verification, ensuring safer financial dealings. Vigilant-E provides a secure and user-friendly database that empowers individuals to actively combat scams and protect themselves and others from financial losses. Vigilant- E's secure database enables proactive scam prevention, magnifying impact through collective contributions. Its innovation lies in user-driven action, distinguishing it from conventional approaches reliant on limited data sources or authorities. This means that fraudulent activities that has not been officially reported to the law enforcement will be captured by Vigilant-E; as long as the social media users reported them, even for small value scams! Vigilant-E holds promising commercial prospects through subscriptions, partnerships, and collaborations with finance or e commerce platforms, attracting cybersecurity backers. As a pivotal tool in fighting online fraud, it entices investors championing safer digital environments.